2019
DOI: 10.1007/s10113-019-01494-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in irrigated agriculture in the Mediterranean region: an overview and spatial analysis of implemented strategies

Abstract: In order to meet future food demand while sustainably managing available land and water resources, irrigated agriculture in semi-arid regions needs to adapt as a response to climate and socio-economic change. In this study, we focus on the Mediterranean region, a dynamic region, which is highly dependent on irrigated agriculture. We provide insight on adaptation strategies implemented on farm level, by doing a systematic review of studies in the region. Our analysis reports 286 implemented adaptations, on 124 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 84 publications
1
36
0
3
Order By: Relevance
“…Hence, the aim of this study is to review the main factors influencing irrigation scheduling and document the impact of ICTs on these factors to identify the conditions that drive the return on investment of various irrigation scheduling methodologies. This review is supported by the analysis of several case studies located in semi-arid areas of Southeast Spain, a country with a 30% of irrigated cropland [37] and most of this area being under Mediterranean natural conditions. The review starts by describing the main factors that should be considered for optimal irrigation scheduling.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Hence, the aim of this study is to review the main factors influencing irrigation scheduling and document the impact of ICTs on these factors to identify the conditions that drive the return on investment of various irrigation scheduling methodologies. This review is supported by the analysis of several case studies located in semi-arid areas of Southeast Spain, a country with a 30% of irrigated cropland [37] and most of this area being under Mediterranean natural conditions. The review starts by describing the main factors that should be considered for optimal irrigation scheduling.…”
Section: Introductionmentioning
confidence: 88%
“…Two treatments were considered: a control (conventional 100% ET c as ET 0 × Kc computations, [37], Kc from [115] and an automated irrigation scheduling based on soil water content values. These were distributed in a completely randomized design with four repetitions per irrigation treatment, each consisting of one row of 13 trees (peach) and six trees (nectarine).…”
Section: Experimental Site and Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to losses caused by changes in temperature, rainfall, and extreme CO 2 concentrations, a sea level rise of 1 m is projected to lead to a loss of one-third of the current agricultural land in the Nile Delta (El-Nahry and Doluschitz 2010). A simulation by Fader et al (2016) suggests that Libya will be unable to meet its irrigation water requirements toward the end of the century, even when the most optimistic scenario of climate change and irrigation technologies are considered (for adaptation options see also Harmanny and Malek 2019). For Morocco, yield losses of around 10% between 2003 and 2050 are projected for the major crop-producing areas under the IPCC A2 scenario without considering a CO 2 fertilization effect.…”
Section: Food Productionmentioning
confidence: 99%
“…Previous studies discovered that, among others, community social status influences access and management to clean water (Ngarava et al, 2019), investment growth can affect the expansion of settlements in coastal areas and have an impact on water quality degradation (Hoque et al, 2019), land use for agriculture is more optimal when carried out in rural areas with consideration of market access and better water availability (Harmanny & Malek, 2019), the majority of the poor finds it difficult to access clean water pipes due to cost issues (Carrard et al, 2019),increasing the ability of the community to manage water resources is needed to reduce social barriers in the use of clean water (Panthi et al, 2019). Meanwhile, this study found the role of access and capacity of the community in reducing the potential for lack of clean water.…”
Section: Components Of Water Povertymentioning
confidence: 99%